Pengaruh Electronic Word Of Mouth (eWOM) Terhadap Minat Beli Followers Instagram Pada Warunk Upnormal - Aditya Ayu Laksmi; Farah Oktafani (STMIK Mardira Indonesia, Bandung, 2016)
Along with the development of technology and information, Warunk Upnormal using social media Instagram as a place for promoting. From the results of the initial survey that researchers do indicate that the many comments that recommends Warunk Upnormal, causing people interested in being followers Instagram of Warunk Upnormal to get information and would like to visit Warunk Upnormal.This study aimed to analyze the effect of Electronic Word of Mouth towards purchase intention of followers instagram Warunk Upnormal. This research includes quantitative research. The method that being used is descriptive -causal. The population in this study is Warunk Upnormal’s Instagram followers. The sampling technique that being used is nonprobability sampling with the sampling purposive sampling. The data collection is done by distributing questionnaires to 400 respondents. Data analysis technique used simple linear regression analysis.Based on the results, it can be concluded that Electronic Word of Mouth has significant effect on purchase intention of followers instagram Warunk Upnormal. This can be seen from the results of the t > t table (8,350 > 1,965942) and significance level, 000 <0.05. Based on the coefficient of determination (R2) calculation can be known the magnitude of the effect of electronic word of mouth (X) variable on purchase intention (Y) was 14.9%. While the remaining 85.1% is influenced by other factors. Keywords: consumer behaviour, electronic word of mouth, purchase intention.